(untitled) (Journal of Libya for geographical studies, 2022)
The research dealt with the study of the Alzawiyah oil port as one of the issues of transportation geography, aiming to identify the geographical factors affecting the establishment and operation of the port, identifying the components of the port and its equipment, and tracking the movement of loading and unloading crude oil and oil derivatives in the port. The descriptive approach has been used to display as well as analyse the port’s components and equipments, also the objective approach which is concerned with the study of the phenomenon, its components, the geographical factors affecting it and its impact on other phenomena; furthermore, the historical approach in tracking the movement of its exports and imports. The researcher concluded a set of results, including : - The importance of the geographical location of the port, as it is located in the area of ​​population concentration in Libya in addition to its proximity to the oil fields in HAMADA and MURZUQ and to Europe - especially ITALY - which imports most of Libya’s production of oil and gas. - It became evident that waves and winds are the most natural conditions affecting the operation of the port. The percentage of the three docks of Alzawiyah port to stop shipping oil and oil derivatives due to bad weather and sea conditions was between 15.08% and 20.95% in 2015.